Experimental nonlocality-based network diagnostics of multipartite entangled states. Issue 1 (December 2017) - Ciampini, Mario; Vigliar, Caterina; Cimini, Valeria; Paesani, Stefano; Sciarrino, Fabio; Crespi, Andrea; Corrielli, Giacomo; Osellame, Roberto; Mataloni, Paolo; Paternostro, Mauro; Barbieri, Marco
Abstract We introduce a novel diagnostic scheme for multipartite networks of entangled particles, aimed at assessing the quality of the gates used for the engineering of their state. Using the information gathered from a set of suitably chosen multiparticle Bell tests, we identify conditions bounding the quality of the entangled bonds among the elements of a register. We illustrate the effectiveness of our proposal by characterizing a quantum resource engineered combining two-photon hyperentanglement and photonic-chip technology. Our approach opens up future studies on medium-sized networks due to the intrinsically modular nature of cluster states, and paves the way to section-by-section analysis of larger photonics resources.